Lung Ultrasonographic Signs in Pulmonary Disease – A Video Review. (February 2023) - Dugar, Siddharth; Fox, Steven; Koratala, Abhilash; Moghekar, Ajit; Mehta, Atul C.
Lung ultrasound (US) is a well-established imaging tool in the inpatient and critical care setting. It has proven its worth in the rapid bedside diagnosis of a variety of conditions pertaining to the lungs and the thorax. Lung US was initially introduced as a bedside imaging tool to evaluate the size and characteristics of pleural effusion. Over the years, the field of lung ultrasonography has rapidly expanded introducing nuances in image interpretation. Numerous primary and secondary signs have been described in the literature to identify both normal and abnormal findings. The primary signs can help narrow the list of differential diagnoses, whereas the addition of secondary signs help create an imaging pattern facilitating the confirmation of diagnosis or recognition of the underlying disease process. These wide variety of signs and patterns can present a challenge to the learning of lung ultrasonography, particularly to a novice user. We sought to compile a comprehensive list of these findings to serve as a useful resource to aid effortless adoption of lung ultrasonography in clinical practice. In this review, we narrate the evolution of lung US, describe common protocols applied in performance of the lung US, and illustrate a comprehensive list of common lung US signs and patterns along with their differential diagnosis and clinical utility.